KOMPETENSI MAHASISWA TARBIYAH SEBAGAI CALON GURU PENDIDIKAN AGAMA ISLAM (PAI) PROFESIONAL DI FAKULTAS TARBIYAH UNIVERSITAS PTIQ JAKARTA - Hidayat, Muhamad Tofik Nur; Shunhaji, Akhmad (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This research found that tarbiyah students who are prospective Islamic religious education teachers at PTIQ University Jakarta have been equipped with five competencies, namely personality competence, pedagogical competence, social competence, professional competence and spiritual competence. This research concludes that the tarbiyah students who are prospective teachers of Islamic religious education at PTIQ University Jakarta have been equipped with the competencies that the author has mentioned above and with the encouragement of professional educators in the tarbiyah faculty at PTIQ University Jakarta, these prospective teachers have the competencies. who is qualified to become a professional Islamic religious education teacher